2022
DOI: 10.3341/kjo.2022.0042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes among Conventional Scleral Fixation, Retropupillary Iris-claw Intraocular Lens Implantation, and Intrascleral Fixation

Abstract: Purpose: To compare the efficacy and safety of conventional scleral fixation, retropupillary iris-claw intraocular lens (IOL) implantation, and intrascleral fixation Methods: This retrospective observational study included 58 patients (58 eyes) who underwent conventional scleral fixation (C-SF, 23 eyes), retropupillary iris-claw IOL implantation (RP-IOL, 23 eyes), and intrascleral fixation (ISF, 12 eyes) by a single surgeon at Samsung Medical Center from October 2017 to July 2020 and were followed up for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Kim et al compared the clinical outcomes among conventional scleral fixation, retropupillary iris-claw IOL implantation, and intrascleral fixation, and resulted the BCVA as 0.08 ± 0.10, 0.08 ± 0.16, and 0.03 ± 0.04 (logMAR) respectively. 14 In the current study, 30% of patients achieved good vision, while 10% of them achieved poor VA in final visit with a mean postoperative BCVA of −0.37 ± 0.27 logMAR. The reason for variability in postoperative BCVA and refractive outcomes in different surgical methods was related to the several factors such as the length, wide and location of scleral tunnel, the shape of the flanged haptic, and the length of the haptic.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Kim et al compared the clinical outcomes among conventional scleral fixation, retropupillary iris-claw IOL implantation, and intrascleral fixation, and resulted the BCVA as 0.08 ± 0.10, 0.08 ± 0.16, and 0.03 ± 0.04 (logMAR) respectively. 14 In the current study, 30% of patients achieved good vision, while 10% of them achieved poor VA in final visit with a mean postoperative BCVA of −0.37 ± 0.27 logMAR. The reason for variability in postoperative BCVA and refractive outcomes in different surgical methods was related to the several factors such as the length, wide and location of scleral tunnel, the shape of the flanged haptic, and the length of the haptic.…”
Section: Discussionsupporting
confidence: 46%
“…Kim et al compared the clinical outcomes among conventional scleral fixation, retropupillary iris-claw IOL implantation, and intrascleral fixation, and resulted the BCVA as 0.08 ± 0.10, 0.08 ± 0.16, and 0.03 ± 0.04 (logMAR) respectively. 14 In the current study, 30% of patients achieved good vision, while 10% of them achieved poor VA in final visit with a mean postoperative BCVA of −0.37 ± 0.27 logMAR.…”
Section: Discussionsupporting
confidence: 46%
“…Most intraocular lens studies often report a POM1 visit as it is an The POM1 visit was also extracted in addition to the final BCVA. Studies have demonstrated that most SSFs require multiple months for complete visual recovery [5,20,[22][23][24][25]29,30]. As such, earlier post-operative visits can be used as a method to assess visual recovery.…”
Section: Data Extractionmentioning
confidence: 99%
“…There was no subgroup analysis carried out for this group as there were only three studies reporting the absolute refractive error. [20,[22][23][24][25][26][27][28][29]31]. The summary mean difference and 95% CI are also shown (according to random-effect estimations).…”
Section: Refractive Outcomes Of Yamane Versus Sutured Scleral Fixationmentioning
confidence: 99%
“…The increased life expectancy and dramatically improved cataract surgery techniques have led to an increase in number of patients undergoing cataract surgery [ 1 ]. The changing lifestyles and advancement in technology have resulted in growing demand for improved visual acuity (VA) without glasses at all distances through cataract surgery [ 2 ].…”
mentioning
confidence: 99%